Proceedings of IEEE International Symposium on Circuits and Systems - ISCAS '94
DOI: 10.1109/iscas.1994.409188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of timing jitter in CMOS ring oscillators

Abstract: In this paper the erects of thennul noise in transistors on riming jitter in CMOS ring-oscillators composed of sourre-coupled differential resistively-louded deluy celLs is investigated. The mlutionship between deluy element design parameters und the inherent thermal noise-induced jitter of the generated wavefonn are unulyzed These results ure compared with simuhed results from U Monte-curlo analysis with good ugreemenr. The unulysk shows that timing jitter is inversely proportional to the squure root of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(118 citation statements)
references
References 5 publications
(1 reference statement)
6
111
0
1
Order By: Relevance
“…The last form of the equation is obtained using the square law model for the transistor current. In [183] an analysis of a differential delay cell yielded similar results. Probably the main finding in this jitter equation is its dependence on inverter DC gain (g m r o ), which is due to the fact that at low frequencies the noise current is transformed into voltage in the output resistance.…”
mentioning
confidence: 64%
“…The last form of the equation is obtained using the square law model for the transistor current. In [183] an analysis of a differential delay cell yielded similar results. Probably the main finding in this jitter equation is its dependence on inverter DC gain (g m r o ), which is due to the fact that at low frequencies the noise current is transformed into voltage in the output resistance.…”
mentioning
confidence: 64%
“…Therefore, because of smaller voltage slew at the input of , the total jitter due to this element at the output will increase [12]. Hence, the values of and in Fig.…”
Section: Generallymentioning
confidence: 98%
“…11(a), the total current consumption of the circuit can be calculated by (11) Here, is the total bias current of the predriver stage which is implemented by a two stage SCL-based buffer [as shown in Fig. 2(a)], and is the bias current of the output LVDS driver: (12) It can be shown that is proportional to the as well as to the voltage swing at the input of LVDS stage called (as depicted in Fig. 11(a)).…”
Section: Power Dissipationmentioning
confidence: 99%
“…Therefore, a design tradeoff exists between compensating DDJ and introducing additional random jitter. From [5], the random jitter introduced through a CMOS buffer stage is (32) where is the load capacitance, is the stage bias current, and is a bias dependent term. The delay of the stage, if slew rate limited as in our cross-coupled stages, is where is the logic swing.…”
Section: Tradeoff Between Data-dependent Jitter Compensation and Rmentioning
confidence: 99%
“…RJ results from the translation of random voltage noise into timing fluctuations due to buffering [5] or phase noise of the transmitter and receiver [6], [7]. On the other hand, DJ has distinct circuit origins and is correlated to limited bandwidth, signal reflection, duty cycle distortion, or power supply noise [8].…”
Section: Introductionmentioning
confidence: 99%